The West African Economic and Monetary Union : Recent Developments and Policy Issues - Hernandez-Cata, Ernesto; Francois, C. (Washington, D.C. : International Monetary Fund, 1998)
Following a serious deterioration of the competitive position of the WAEMU region in the 1980s and the eary 1990s, the countries took steps that have led to a significant turnaround in economic activity, a drop in inflation, and increases in output, exports and investment. This study describes policy issues that the region continues to face and suggests how the WAEMU countries can address them.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet